2010
DOI: 10.1097/wnf.0b013e3181e77428
|View full text |Cite
|
Sign up to set email alerts
|

Substitution Profile of the Cannabinoid Agonist Nabilone in Human Subjects Discriminating Δ9-Tetrahydrocannabinol

Abstract: These data demonstrate that the interoceptive effects of nabilone are similar to Δ-THC in cannabis users. The overlap in their behavioral effects is likely due to their shared mechanism as CB1 receptor agonists. Given the relative success of agonist replacement therapy to manage opioid, tobacco, and stimulant dependence, these results also support the evaluation of nabilone as a potential medication for cannabis-use disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 65 publications
5
33
0
Order By: Relevance
“…These results are concordant with the ability of CB agonists to impact VDCC function via CB 1 receptor mediated G-protein activation as well as CB-receptor-independent mechanisms (Howlett et al, 2010; Lozovaya et al, 2009). In previous studies, drug discrimination procedures like those used here revealed that the cannabinoid agonist nabilone substituted for Δ 9 -THC, but the dopamine/norepinephrine reuptake inhibitor methylphenidate, the opioid agonist hydromorphone and the GABA A positive allosteric modulators triazolam and diazepam did not, demonstrating the pharmacological selectivity of the Δ 9 -THC discrimination (Lile et al, 2009, 2010, 2014). The present results support this selectivity by demonstrating Δ 9 -THC stimulus generalization to a compound having a common neurobiological target.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…These results are concordant with the ability of CB agonists to impact VDCC function via CB 1 receptor mediated G-protein activation as well as CB-receptor-independent mechanisms (Howlett et al, 2010; Lozovaya et al, 2009). In previous studies, drug discrimination procedures like those used here revealed that the cannabinoid agonist nabilone substituted for Δ 9 -THC, but the dopamine/norepinephrine reuptake inhibitor methylphenidate, the opioid agonist hydromorphone and the GABA A positive allosteric modulators triazolam and diazepam did not, demonstrating the pharmacological selectivity of the Δ 9 -THC discrimination (Lile et al, 2009, 2010, 2014). The present results support this selectivity by demonstrating Δ 9 -THC stimulus generalization to a compound having a common neurobiological target.…”
Section: Discussionsupporting
confidence: 51%
“…To further investigate potential similarities, particularly as they relate to the abuse-related interoceptive effects of cannabis, the present study determined the separate and combined effects of gabapentin and Δ 9 -tetrahydrocananbinol (i.e., Δ 9 -THC, the primary active constituent of cannabis) using pharmacologically selective drug-discrimination procedures (Lile et al, 2009, 2010, 2012, 2014). Gabapentin was hypothesized to occasion Δ 9 -THC-like discriminative-stimulus alone and shift the discriminative-stimulus effects of Δ 9 -THC leftward/upward when administered concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that women had elevated heart rate and lower skin temperature relative to men is consistent with previously documented differences in women and men for these physiological outcomes (Christensen et al, 2012; Ryan et al, 1994; Umetani et al, 1998). Another possibility is that chronic cannabis administration might result in further sex-based separation in baseline heart rate and skin temperature, considering that these measures are sensitive to acute cannabinoid administration (e.g., Lile et al, 2010b). …”
Section: Discussionmentioning
confidence: 99%
“…Fraser7 also noted in this study that nabilone increased sleep time and was not associated with the development of tolerance. Another study by Lile et al8 found similar interoceptive effects of nabilone compared with delta-9-tetrahydrocannabinol, which lead the authors to conclude that nabilone may be useful as a harm reduction approach to reduce use of smoked cannabis in cannabis-dependent individuals similar to the use of agonists in tobacco and opioid dependence. Of note, in an extensive search of scientific literature, popular press, and focused interviews with medical professionals and law enforcement officials, Ware and St Armand9 found little evidence for nabilone abuse, including in Canada where it has been available for over 30 years.…”
mentioning
confidence: 94%